Reception of the Warsaw Autumn Festival in Lithuania: Cultural Discourse and Political Context - Stanevičiūtė Rūta (Musicology Today, 2017)
This article aims to offer a broader understanding of the Lithuanian reception of the Warsaw Autumn festival in relation to the modernisation of national music in Lithuania since the late 1950s – early 1960s. Based on a micro-historical and comparative approach to the network of individuals and events, it is intended to explore the shifts of reception through analysis of musical criticism, composers’ work and discourse, and artistic exchange between the Lithuanian and Polish new music scenes. The author discusses the cultural and political factors which affected the changing role of the Warsaw Autumn festival and its impact on the modernisation processes in Lithuanian music. In addition, the asymmetries of mutual understanding and interests between the Polish and Lithuanian music cultures have been highlighted both during the Cold War and the post-communist transformation periods.